Online Marketing Communication of Polish Cities During The COVID-19 Pandemic - Agata NIEMCZYK; Aneta OLEKSY-GĘBCZYK (Communications of International Proceedings, 2021)
The COVID-19 pandemic has changed the functioning of almost all market actors. Most of them, including local government units, have reformulated communication with the public. The aim of the article is to show that the COVID-19 pandemic has changed the online marketing communication of cities with their stakeholders. To achieve this goal, theoretical and empirical considerations were made using research methods typical of this type of studies: critical analysis of the subject literature, as well as analysis of available secondary empirical data using principal component analysis, silhouette analysis, and hierarchical cluster analysis. Own research has proven transformations in clusters grouping Polish cities based on similarities in marketing communication with stakeholders. The transformations in question are the most numerous (most cities switch clusters) and pertain to the period before and during the pandemic (e.g. March-April 2019 vs March-April 2020), compared to the periods before the pandemic (January-February 2019 vs January-February 2020) when such a notable shift is not noted.
Keywords: Online Marketing Communication; City; Principal Component Analysis; Silhouette Analysis; Hierarchical Cluster Analysis